Treatment of mandibular osteoradionecrosis by periosteal free flaps. Issue 6 (July 2019) - Bettoni, J.; Olivetto, M.; Duisit, J.; Caula, A.; Bitar, G.; Lengele, B.; Testelin, S.; Dakpé, S.; Devauchelle, B.
Abstract: Mandibular osteoradionecrosis (ORN) is one of the most serious complications of radiotherapy of the head and neck, and is characterised by hypoxia, hypovascularisation, and hypocellularity. Periosteal free flaps have intrinsic osteogenic, and extrinsic neoangiogenic, properties that are related to the periosteum. Our objective was to present our experience with the use of periosteal free flaps in the treatment of ORN (Notani class I or II) that are refractory to conservative management or have a large area of bone (≥2 cm) exposed. We organised a single-centre, retrospective study between 2003 and 2013 and describe the management of 11 patients (4 women and 7 men) who were being treated for refractory mandibular ORN. Thirteen periosteal free flaps were used: inner femoral condylar periosteum (n = 4), iliac crest (n = 1), external brachial with humeral periosteum (n = 1), and forearm with radial periosteum (n = 7). During follow-up we found three acute complications (haematoma, partial necrosis, and total vascular necrosis) that required immediate construction of a second periosteal free flap. There were also two chronic complications (fistula and post-traumatic fracture). With only one progressive lesion identified, the ORN was stopped in 11/12 patients. Two examples of osteoconduction were identified on postoperative images at six months and two years. Because of its osteoconductive and neoangiogenic capacities, the periosteal free flap seems to offer a real biological dimension to the treatment of ORN, and its efficiency favours its early revascularisation.